Exploring Potential and Business Ideas in Pelajau Ilir Village - Tika Handayani; Sunanto Sunanto; Adellia Suhermanto; Shally Rizkiyanti; Leni Sabrina (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2024)
This activity is carried out with the aim of raising awareness among the community of Pelajau Ilir Village about the importance of exploring both personal and environmental potentials, thereby creating opportunities in the form of business ideas. The form of this activity is to socialize with the community about the importance of exploring potentials, utilizing the surrounding environment to create opportunities for progress towards a better life. This is done because there is still reluctance among the community to improve socio-economic life, and self-empowerment has not been fully implemented. So far, most residents of Pelajau Ilir Village have relied solely on one source of income, which is rubber plantations dependent on nature alone. Through this Community Service activity 'Exploring Potentials and Business Ideas', it is hoped that information on how communities can be motivated to progress and utilize local opportunities will be obtained. The implementation of this activity is carried out by disseminating information on how to explore personal potentials, local environmental potentials, and utilize opportunities to generate business ideas. The result of this activity is that the community gains a better understanding of the importance of exploring potentials, creating business ideas for additional income, and improving their quality of life. Additionally, this activity is expected to serve as a recommendation and guidance for the local government or relevant agencies to direct or empower communities to develop themselves, and provide facilities and support to create self-reliant communities.